PENGEMBANGAN HANDOUT BERGAMBAR DILENGKAI PETA PADA MATERI ALAT INDERA UNTUK SMP - Pradipta, Enggia; Helendra, Helendra; Wati, Meliya (STKIP PGRI Sumbar, 2014)
ABSTRACT This research is a research development, and the final outcome of this research is a product handout. Handout is a education media that contains of learning materials which arranged in a systematic, operasional and directed. Beside it that also comes with the picture completed with concept mapping. By using biology student worksheets it will facilitate students in understanding the material. This picture handout with completed with concept mapping facilitate students in understanding the theory. This research has four stages, namely definition, design, development and dessiminate . Based on the result obtained, it can be concluded that the handout has developed valid and practical, therefore handout can already be used at the time of learning.Keyword :